Pengaruh Strategi Promosi Melalui Sosial Media terhadap Keputusan Pembelian : Survei pada Konsumen Wardah di Muara Kosmetik Tasikmalaya - Muhamad Gifar Arsyad Gundara; Budhi Wahyu Fitriadi; Barin Barlian (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This research aims to find out how the promotional strategies evidence through social media and the effect of promotional strategies through social media toward purchasing decisions. The survey was conducted on 100 respondents, the aged over 18 years, and who had purchased Wardah cosmetic at Muara Kosmetik Tasikmalaya by using a questionnaire as the main data collection.  The data were analyzed by using several formulas in quantitative methods such as validity test, reliability test, linear regression, and coefficient of determination which is assisted by software IBM SPSS Statistics 24. The result of analyzing data shows that social media can facilitate the consumers to obtain the information related to the products offered and product information to be purchased by consumers. Besides being able to facilitate the dissemination of information, the companies also facilitated to buy and sell online by using promotional strategies through social. By carrying out promotional strategies through social media, it possibly evidences the consumers purchasing decision in buying wardah cosmetic at Muara Kosmetik Tasikmalaya positively and significantly.